Match analysis within the coaching process: a critical tool to improve coach efficacy - Fernandez-Echeverria, C.; Mesquita, I.; González-Silva, J.; Claver, F.; Moreno, M. P. (International Journal of Performance Analysis in Sport, 2017)
Match analysis is a topic of current interest in sports science. It is widely used across a range of different sports and has, in the process, demonstrated a number of different performance indicators. For sports coaches, match analysis is perhaps one of the most important tools for analysing games and extracting valuable information about their own and opposing teams. However, despite the usability of this tool, little is known about how information obtained from game analyses affects the planning of training, the setting of goals and the choice of strategic approach by coaches. It is therefore necessary to conduct case studies which evaluate the usefulness of match analysis in an applied context such as high-level sport. This review has two main goals: (1) To provide an overview of empirical studies of match analysis in Volleyball; and (2) to attempt to demonstrate the benefits of using match analysis as a support tool for sports training, and the need to develop studies which analyse the use of this tool and its influence on high-level training processes.